Risk of adverse cardiovascular events based on common genetic variants in 8-year follow-up of the LIPIDOGEN2015 population using the polygenic risk score (PRS): study design and methodology - Maciej Banach; Martyna Fronczek; Tadeusz Osadnik; Agnieszka Gach; Dominik Strapagiel; Marcin Słomka; Mateusz Lejawa; Anna Goc; Ewa Boniewska-Bernacka; Anna Pańczyszyn; Gregory Y.H. Lip; Dimitri P. Mikhailidis; et al. (Archives of Medical Science)
Introduction Classical risk factors such as hypertension, hypercholesterolemia, pre-diabetes, diabetes and obesity can predict adverse cardiovascular events, but they are less prognostic in patients aged < 60 years. Polygenic risk scores (PRS) can be effective in predicting adverse coronary events in younger and middle-aged patients. Our main aim is to assess the utility of a new PRS created for the Polish population in predicting mortality during an 8-year follow-up in the nationwide LIPIDOGEN2015 population.